Effect of non‐migrating bars on dune dynamics in a lowland river. Issue 6 (12th March 2020) - de Ruijsscher, T. V.; Naqshband, S.; Hoitink, A. J. F.
Abstract: As dunes and larger‐scale bed forms such as bars coexist in rivers, the question arises whether dune dynamics are influenced by interaction with the underlying bed topography. The present study aims to establish the degree to which dune characteristics in two and three dimensions are influenced by an underlying topography dominated by non‐migrating bars. As a case study, a 20 km stretch in the Waal River in the Netherlands is selected, which represents a sand‐bed lowland river. At this location, longitudinal training dams (LTDs) have recently been constructed to ensure sufficient navigation depth during periods with low water levels, and to reduce flood risk. By using data covering 2‐year‐long periods before and after LTD construction, the robustness of the results is investigated. Before LTD construction, dune characteristics show large variability both spatially and temporally, with dunes being longer, lower, less steep and having a lower lee side angle when they are located on bar tops. The correlation between dune characteristics and the underlying bed topography is disrupted by unsteady conditions for which the dunes are in a state of transition. The bar pattern causes tilting of dune crest lines, which may result from a transverse gradient in bedload sediment transport. As a result of LTD construction, the hydraulic and morphological conditions have changed significantly. Despite this, the main conclusions still hold, which strengthens the validity of the results. ©2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : Subaqueous dunes exist superimposed on non‐migrating bars in the Waal River, The Netherlands, which represents a sand‐bed lowland river. Dunes on bar tops are lower, longer, less steep and have a lower lee side angle than those in the pools. When migrating over bars, dune fronts become increasingly tilted, which is attributed to a transverse gradient in bed load sediment transport.